MODEL KOOPERATIF TIPE TEAMS GAMES TOURNAMENT BERBANTU MONAKU PENGARUHNYA TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Anna, Jesica Martogi; Sumaryati, Sri (Universitas Tanjungpura, 2025)
This study analyzes the influence of the Teams Games Tournament (TGT) cooperative learning model assisted by the Accounting Monopoly (MONAKU) media on students' critical thinking skills in learning accounting for trading companies. The research method used is a quasi-experimental design with a non-equivalent control group. The research sample consisted of two XI Accounting classes at SMK Negeri Jumantono, selected randomly. The research results show that the application of the TGT model assisted by MONAKU significantly improves students' critical thinking skills compared to the Discovery Learning model. This is evidenced by the analysis of independent t-tests and N-Gain tests, which show a higher average increase in critical thinking scores in the experimental class compared to the control class. Thus, the MONAKU-assisted TGT model can be an effective strategy in enhancing students' critical thinking skills in accounting subjects.